Role of healthcare-facilities layout design, healing architecture, on quality of services - Parsia, Yasaman; Puteri Fadzline, Muhamad Tamyez (IAEME Publication, 2018)
These days, new and serious problems in field of healthcare, such as, increasing rate of infections, are alarming. Therefore, quality of treatment and health care services are even more vital than past. There are different elements which can be affected the quality of healthcare services. One of the most important element is healthcare facility (HF) layout design. If a HF presents good services of treatment by a specialized person in an inconvenient physical environment, it will increase healthcare risks such as infection, financial burden and low patient satisfaction. Based on a mini-literature review, this study tried to introduce the important of healthcare facility layout design and its role in quality of HF services. As a result, this study showed that HF with appropriate layout design can have a better outcome than the other one with unacceptable layout design. Therefore, it seems so necessity for all HFs and also government to put an appropriate attention, standard and guide to the beginning phase of HF building construction by a better layout design. Proper layout design decreases HF risks and increase customer satisfaction and service quality.